Intrinsic diffusion sensitivity of the balanced steady‐state free precession (bSSFP) imaging sequence. (7th September 2015) - Bär, Sébastien; Weigel, Matthias; von Elverfeldt, Dominik; Hennig, Jürgen; Leupold, Jochen
<x xml:space="preserve">Abstract</x> The purpose of this work was to analyze the intrinsic diffusion sensitivity of the balanced steady‐state free precession (bSSFP) imaging sequence, meaning the observation of diffusion‐induced attenuation of the bSSFP steady‐state signal due to the imaging gradients. Although these diffusion effects are usually neglected for most clinical gradient systems, such strong gradient systems are employed for high resolution imaging of small animals or MR Microscopy. The impact on the bSSFP signal of the imaging gradients characterized by their b‐values was analyzed with simulations and experiments at a 7T animal scanner using a gradient system with maximum gradient amplitude of approx. 700 mT/m. It was found that the readout gradients have a stronger impact on the attenuation than the phase encoding gradients. Also, as the PE gradients are varying with each repetition interval, the diffusion effects induce strong modulations of the bSSFP signal over the sequence repetition cycles depending on the phase encoding gradient table. It is shown that a signal gain can be obtained through a change of flip angle as a new optimal flip angle maximizing the signal can be defined. The dependency of the diffusion effects on relaxation times and b‐values were explored with simulations. The attenuation increases with T2. In conclusion, diffusion attenuation of the bSSFP signal becomes significant for high resolution imaging voxel size (roughly < 100 μm) of long T2 substances. Copyright © 2015 John Wiley & Sons, Ltd.